Study on Integrated Energy System Scheduling Optimization Based on Runoff Algorithm. Issue 1 (February 2020) - Yuan, Wenwei; Yuan, Shuhua; Luo, Jinman
Abstract: With the advancement of economic globalization, set energy production, supply and use of integrated energy system has become the current social indispensable material base, its advantage is to utilize the energy such as natural gas, wind energy, solar energy is transformed into each other basic conditions, based on the use of renewable function between the electric energy development model, in order to reduce harmful emissions and effectively promote the consumption of energy storage, supply and its efficiency for the development goals, finally realizes the comprehensive optimization of energy system operation and development. However, the practice based on integrated energy scheduling can not achieve the best expected results, and there is a paradox between the theoretical basis and the fact. Therefore, based on the study of integrated energy system scheduling optimization, combined with different research status at home and abroad, this paper proposes a runoff algorithm to realize the economic operation mode of energy system, in order to solve the problems in the implementation process of integrated energy system scheduling, and promote the development trend of high efficiency and stability.